Effects of Pressure and Press Time on the Physical Quality of Dried-Frozen Tofu (Tribhuvan University Journal of Food Science and Technology, 2023)
This study aimed to produce tofu from locally sourced white soybeans (Glycine max L. Merr.) by employing varying pressure and press time parameters, ranging from 1 to 5 kg/cm2 and 8 to 90 min, respectively. Employing a robust experimental design (Central composite design, face centered, 2-factor, 3-level, with 13 runs), facilitated through Design Expert® v 10.0.1, a design of experiment (DOE) tool, enabled a systematic exploration of the processing space. Following production, the fresh tofu batches underwent a freezing stage at -20°C for 7 days, subsequent thawing in water (at 50°C for 30 min), and final drying in an electric oven at 75°C until reaching a moisture content of 10%. Response surfaces were meticulously generated to comprehensively understand the intricate interplay between pressure, press time, and key responses, such as rehydration ratio, pore size, and bulk density. A thorough data analysis, utilizing Design Expert® v 10.1.1 for pore size and rehydration ratio, and Genstat® v 12.0.1 for textural attributes, revealed statistically significant (p≤0.05) impacts of processing variables on the sensory attributes of tofu. Leveraging desirability constraints aimed at minimizing pressure, press time, and pore size while maximizing rehydration ratio, the optimized conditions were determined as 3.91 - 4.16 kg/cm2 for pressure and 8.0 min for press time. Under these optimal conditions, the resulting dried-frozen tofu exhibited a maximum rehydration ratio of 0.275 mm and an average internal pore size of 1.335. These findings not only contribute valuable insights into the tofu production process but also offer a practical guide for enhancing the quality of dried-frozen tofu while minimizing resource inputs. This optimized approach holds promise for efficient and sustainable large-scale tofu manufacturing.